2011
DOI: 10.1088/1674-1056/20/1/010311
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Bose—Einstein condensate in a harmonic potential and a Gaussian energy barrier

Abstract: We have studied the dynamics of Bose-Einstein condensate by solving numerically the Gross-Pitaevskii (GP) equation. We examined the periodic behaviour of the condensate in a shifted harmonic potential, and further demonstrated the tunneling effect of a condensate through a Gaussian energy barrier, which is inserted after the condensate has been excited by shifting the harmonic trapping potential to a side. Moreover, it is shown that the initial condensate evolves dynamically into two separate moving condensate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…[12,13] In Ref. [7] we have studied the tunneling effect of a condensate on a barrier by initiating the condensate and removing the harmonic trapping potential. It is shown that two moving condensates can be ob-tained after the tunneling time.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[12,13] In Ref. [7] we have studied the tunneling effect of a condensate on a barrier by initiating the condensate and removing the harmonic trapping potential. It is shown that two moving condensates can be ob-tained after the tunneling time.…”
mentioning
confidence: 99%
“…Due to the combination of the harmonic potential and the barrier, the interference fringes are more intensive than those without trapping potential in Refs. [7] and [22] and are more suitable for detection. Tunneling effect can be nearly suppressed when the energy barrier is increased to a certain degree.…”
mentioning
confidence: 99%
“…We then apply a symplectic algorithm to it, and the normalization of the wavefunction is naturally preserved. [14][15][16] In this paper, the Euler-centered scheme is applied, [16] the space step is h = 0.1, and the boundary is taken to be |ξ | max = 20. The time step is τ = 0.001, the computation time is from 0 to 5.0 × 10 3 , and the total computation step is 5.0 × 10 6 .…”
Section: Numerical Modelmentioning
confidence: 99%
“…The symplectic method can preserve the symplecic structure of the nonlinear system and the normalization of the wavefuction is naturally preserved in computation, which is superior to some other methods in long-time and many-step computation when applied to nonlinear differential equations. [14][15][16] A periodic driving force is an efficient and effective tool for studying the behavior of condensate. For BEC in a harmonic trapping potential, the effect of resonance can either be studied by modulating the trapping frequency periodically, or by modulating the interaction between the atoms periodically.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the preparation and quantum control of cold (T > 1 mK) and ultracold (T < 1 mK) molecules have captured much attention of researchers and been one of the most active research subjects in the atomic and molecular physics. [1][2][3][4][5][6] Ultracold molecules have been applied in many fields such as testing fundamental physical constants, [7] precision spectroscopy, [8] and quantum-information processing. [9] Particularly, highly dense samples of molecules in the ground rovibrational state (ν = 0, J = 0) are required in many applications.…”
Section: Introductionmentioning
confidence: 99%